2011
DOI: 10.1021/jp210636j
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Nondissociative Binding of N2O on Oxygen Vacancies on a Rutile TiO2(110)-1×1

Abstract: The interaction of N2O with oxygen vacancies (VO’s) on a partially reduced rutile TiO2(110)-1×1 surface was investigated using temperature-programmed desorption (TPD). Contrary to a common belief that VO on a rutile TiO2(110) is a dissociation site for N2O, our results indicate that N2O does not dissociate to form N2(g) and O(a). In TPD, N2O desorption shows two peaks with maxima at 135 and 175 K that are assigned to N2O desorption from Ti4+ and VO sites, respectively, with absolute coverages determined to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
(92 reference statements)
1
20
0
Order By: Relevance
“…However, the loss of an oxygen atom requires a sufficiently long N 2 O residence time at an oxygen vacancy; otherwise, it can desorb as N 2 O (gas) (step 12). Kim et al reported that N 2 O does not dissociate on TiO 2 surface to form N 2 and O. Moreover, it has been reported that N 2 O molecules are only weakly bound to the TiO 2 surface with an adsorption energy of 7.73 kcal/mol; thus, it is likely that in this photocatalyzed reaction most of the N 2 O (ads) were desorbed as N 2 O (gas) to yield the observed MS signal at m / z 44.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, the loss of an oxygen atom requires a sufficiently long N 2 O residence time at an oxygen vacancy; otherwise, it can desorb as N 2 O (gas) (step 12). Kim et al reported that N 2 O does not dissociate on TiO 2 surface to form N 2 and O. Moreover, it has been reported that N 2 O molecules are only weakly bound to the TiO 2 surface with an adsorption energy of 7.73 kcal/mol; thus, it is likely that in this photocatalyzed reaction most of the N 2 O (ads) were desorbed as N 2 O (gas) to yield the observed MS signal at m / z 44.…”
Section: Resultsmentioning
confidence: 94%
“…However, the loss of an oxygen atom requires a sufficiently long N 2 O residence time at an oxygen vacancy; otherwise, it can desorb as N 2 O (gas) (step 12). Kim et al 14 13 thus, it is likely that in this photocatalyzed reaction most of the N 2 O (ads) were desorbed as N 2 O (gas) to yield the observed MS signal at m/z 44.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…With an increasing number (> 10) of sputter-anneal cycles, the TiO 2 (110) crystal turned dark blue and the V O concentration increased to ~5% (~2.6 × 10 13 cm -2 ) (this sample is referred to as r-TiO 2 ). We have also prepared hydroxylated [22][23][24] and oxidized [25,26] [27]. The absolute NO dose(in NO/cm 2 ) was estimated from the plot of integrated area of NO TPD spectra obtained from multilayers of NO dosed on oxidized TiO 2 against the calibrated dose of NO by assuming that the sticking coefficient is unity at the dose temperature.…”
Section: Methodsmentioning
confidence: 99%